2023
DOI: 10.1111/codi.16541
|View full text |Cite
|
Sign up to set email alerts
|

The development and implementation of an interactive application for new ostomy patients

Abstract: Aim Guidance throughout the entire process of ostomy surgery is warranted to improve self‐management and reduce healthcare consumption. The aim of this study was to develop an interactive application to educate patients scheduled for ostomy surgery and to evaluate patient satisfaction and implementation. Method A literature study and a cross‐sectional study among patients and nurses was performed to evaluate the relevance of different topics (e.g., ostomy materials, self‐care, complications, impact) for an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Ghafouri also emphasizes in his study the up-to-date and preparation of the contents provided in the software under the supervision of experts [ 17 ]. Also, in their research, Ketelaers et al emphasized the preparation of appropriate and specialized content under the supervision of experts in each field [ 27 ]. Therefore, it is necessary to update these programs as well as the accuracy and accuracy of their information under the supervision of experts and scientific associations [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghafouri also emphasizes in his study the up-to-date and preparation of the contents provided in the software under the supervision of experts [ 17 ]. Also, in their research, Ketelaers et al emphasized the preparation of appropriate and specialized content under the supervision of experts in each field [ 27 ]. Therefore, it is necessary to update these programs as well as the accuracy and accuracy of their information under the supervision of experts and scientific associations [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Ketelaers et al emphasize that a specific approach for the patient can further improve the quality and perceived value of the program, so they suggested that the software that provides patient-centered education is effective in educating the patient [ 27 ]. Taking into account the feedbacks that was provided in the self-assessment based on the conditions of each patient in the current research software, it can be said that their results are similar to the current research, and the software that can be used with the data bank can help the patient in care.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by reducing the need for visiting nurse services, there could be a more important role for ostomy nurses. Optimized guidance, even after discharge, may also be achieved with tailor-made and innovative healthcare solutions such as interactive applications, which have recently been developed and evaluated in a similar group of patients with promising results [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%